2013
DOI: 10.1111/ijcp.12045
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of clinical outcomes of α-blocker or finasteride monotherapy followed by combination therapy: determination of the period of combination therapy of α-blocker and finasteride

Abstract: Discontinuation of alpha-blockers or finasteride after combination therapy for ≥ 6 months maintained improvements in symptoms. The appropriate period of combination therapy was ≥ 9 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The best effect in reducing the progression of BPH is seen in PV > 35mL and PSA > 2.0 ng/mL 25 . Symptoms improved by combination therapy and maintained after discontinuation of AB and continuous administration of 5-ARI monotherapy, whereas the risk of urinary retention due to the re-growth of the prostate is reduced 26 .…”
Section: Discussionmentioning
confidence: 98%
“…The best effect in reducing the progression of BPH is seen in PV > 35mL and PSA > 2.0 ng/mL 25 . Symptoms improved by combination therapy and maintained after discontinuation of AB and continuous administration of 5-ARI monotherapy, whereas the risk of urinary retention due to the re-growth of the prostate is reduced 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Among 33 men who initially experienced symptomatic improvement with α 1 -blocker monotherapy, mean symptom severity were not increased up to 6 months after unblinded discontinuation and more than two-thirds of men remained off medication (39). Another unblinded study among 75 men with symptomatic improvement after α 1 -blocker monotherapy demonstrated stable symptoms for up to 12 months after discontinuation with only 30% of men requesting re-initiation of treatment (40). Even among men with more severe LUTS who are treated with combined α 1 -blockers plus 5α-reductase inhibitor therapy, both observational and randomized studies have demonstrated no symptomatic progression in the majority of men who discontinue α 1 -blockers but continue 5α-reductase inhibitor monotherapy (41-44).…”
Section: Discussionmentioning
confidence: 99%
“…Another unblinded study among 75 men with symptomatic improvement after α 1 -blocker monotherapy demonstrated stable symptoms for up to 12 months after discontinuation with only 30% of men requesting re-initiation of treatment ( 40 ). Even among men with more severe LUTS who are treated with combined α 1 -blockers plus 5α-reductase inhibitor therapy, both observational and randomized studies have demonstrated no symptomatic progression in the majority of men who discontinue α 1 -blockers but continue 5α-reductase inhibitor monotherapy ( 41 44 ). In the largest randomized clinical trial of 230 men receiving combined therapy who were assigned to discontinue either 5α-reductase inhibitor or α 1 -blocker, 74% of men in both groups had no worsening of symptoms after 12 months ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some interventions to improve TWOC outcomes, such as medication, often require long periods of time to take full effect (Fisher et al 2014;Joint Formulary Committee 2022). Patients can become unhappy and frustrated with their indwelling catheter and may request their TWOC takes place sooner, not allowing for the full effectiveness of the intervention to take place (Son et al 2013;Vlotman-Novinuk 2019). This could cause another failed TWOC.…”
Section: Other Benefits Of Catheter Valvesmentioning
confidence: 99%